Green and efficient two-step degradation approach for converting Powder River Basin coal into fuels/chemicals and insights into their chemical compositions. (15th April 2020) - Liu, Fang-Jing; Liu, Guang-Hui; Gasem, Khaled A.M.; Xu, Bang; Goroncy, Alexander; Tang, Ming-Chen; Huang, Zai-Xing; Fan, Maohong; Wei, Xian-Yong
Graphical abstract: Highlights: Green and efficient two-step degradation produced high yield high-value products. First-step degradation has high energy recovery and low energy consumption ratio. Liquid tar was separated into light oil and asphaltene with different applications. Various oxygenated components were revealed in liquid tar and its sub-fractions. Valuable aliphatic acids were produced from mild oxidation of the residue. Abstract: A green and efficient two-step degradation approach, including supercritical CO2 /ethanol degradation and oxidation in aqueous hydrogen peroxide solution, was reported to convert Powder River Basin coal into fuels/chemicals. In total, 43.5 wt% liquid tar and 23.3 wt% oxidation products were obtained from the two-step degradation. The liquid tar was facilely separated into light oil and asphaltene, with yields of 27.3 wt% and 16.5 wt%, respectively. The first-step degradation has high energy recovery (50%) and low energy consumption ratio (minimum 0.17), indicating an energetic net energy gain. The light oil is a promising feedstock as clean liquid fuels due to its high H/C ratio (1.58) and heating value (34.56 MJ/kg). The asphaltene with lower H/C and O/C ratios but higher aromaticity (0.83) could be a good precursor for carbon materials. The light oil can be upgraded into clean liquid fuels by hydrodeoxygenation or used as feedstock for producing oxygenated chemicals because it is rich in oxygenated components. Phenols and aliphatic esters account for 74.2% of the volatile components in the light oil. High resolution mass spectrometric analysis revealed that the O1 –O4 class species are dominant components with relative abundance of 71% in the light oil. Valuable carboxylic acids with total yields of 19.7 wt%, especially alkanedioic and alkanetricarboxylic acids, were produced from oxidation of the scCO2 /ethanol degradation residue, which is a promising second-step degradation to utilize the residue. This study provides an efficient coal conversion processes for producing fuels/chemicals and reducing energy consumption and environmental impact.